PERANCANGAN DESAIN PENGALAMAN TURISTIK MELALUI ECOTOURISM RUMAH ADAT BALI KUNO DI DESA MANGESTA KECAMATAN PENEBEL KABUPATEN TABANAN PROPINSI BALI - R.M. Pramutomo R.M. Pramutomo (Universitas Gadjah Mada, 2013)
This article based on the research’s result of empowering the traditional architecture in Bali calledBale Mundhak. The Bale Mundhak originally is a traditional house which is potentially related to itsactivities inside the building and surround it. Several problems had known and it has been indicatedby some proposed research. Some of them presented through this article as a result of the first yeartarget of the research proposition. Through this article the propose will be answered identificationof Bale Mundhak’s function as a traditional house in Mangesta village, district Penebel of Tabananregion in Bali. In other side this article will also strives identification several social and cultural activitiesinherence to the traditional function of Bale Mundhak as a rites location. And the last proposition thisarticle will also examines the Bale Mundhak and its function related to the special arts activities in danceand gamelan music. All the propose research will expose a creative industry based on tourist villageby empowering Bale Mundhak as a traditional house in Mangesta village and its arts activities which issupporting human resources surround the village based on ecotourism inclusively